107k views
4 votes
2(x+4)+(x+1)=6(2x) solve for x

User Satyan
by
5.1k points

1 Answer

1 vote

Explanation:


{:}\longrightarrow
\sf 2 (x+4)+(x+1)=6 (2x)


{:}\longrightarrow
\sf 2x+8+(x+1)=12x


{:}\longrightarrow
\sf 2x+8+x+1=12x


{:}\longrightarrow
\sf 2x+x+8+1=12x


{:}\longrightarrow
\sf 3x+9=12x


{:}\longrightarrow
\sf 12x=3x+9


{:}\longrightarrow
\sf 12x-3x=9


{:}\longrightarrow
\sf 9x=9


{:}\longrightarrow
\sf x={\frac {9}{9}}


{:}\longrightarrow
\sf x=1

User Dean Peters
by
4.9k points